Metagenomic Characterization of Heavy Metal-Fungal Microbiota Interaction in Pinus brutia Needles - Çebi Kılıçoğlu, Melike (Turkish Journal of Agriculture - Food Science and Technology, 2024)
Fungi are considered an effective method as an alternative solution in the biological remediation of heavy metals. The aim of the study was to determine comparative heavy metal concentrations in Pinus brutia needles taken from Samsun Organized Industrial Zone which have been contaminated with heavy metals for a long time and Adalar Forest region, and to evaluate the fungal mycobiome that could be potential bioremediators. As a result of the study, Cu, Pb, Zn, Mn, Cr, Cd, Ni, Se, As, Li, V and Co elements were analyzed in the needle samples, and the concentrations of Ni, As, Li, V and Co among these elements remained below the detectable limits. For all other elements, the concentrations obtained in the industrial zone was higher than the concentrations obtained in the Adalar region. In addition, as a result of metagenomic analysis, Aureobasidium (27.5%), Gibberella (20.7%), Cladosporium (14%), Articulospora (5.8%), Helicoma (3.1%), Alternaria (1.7%), Hazslinszkyomyces (1.6%) and Lasiodiplodia (1%) were determined in Samsun OIZ Pinus brutia needles, respectively. Phaeococcomyces (22.8%), Hormonema (19.1%), Aureobasidium (13.8%), Cladosporium (6.5%), Alternaria (4.6%), Neosetophoma (%3.1). Rachicladosporium (3%), Ophiosphaerella (2.1%), and Phaeosclera (1.8%) were determined in the Samsun Adalar mycobiome, respectively. The results show that taxa known to be resistant to excess element concentrations are dominant in the environment. In the future, this study may serve as a reference for the development of innovative strategies for remediation of heavy metal pollution using biological resources for a sustainable and clean environment.